2000
DOI: 10.1086/315378
|View full text |Cite
|
Sign up to set email alerts
|

Related Strains ofMycobacterium aviumCause Disease in Children with AIDS and in Children with Lymphadenitis

Abstract: Sequence analysis of the ribosomal internal transcribed spacer of 56 Mycobacterium avium complex isolates from pediatric patients with AIDS or lymphadenitis revealed (similar to the situation in adults) that the closely related Mav-B and Mav-A sequevars caused the vast majority of disease. IS1245 restriction fragment-polymorphism analysis and pulsed-field gel electrophoresis revealed sets of isolates with closely related patterns among strains from patients in the Boston area and among isolates from Los Angele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The majority of cases of MAC lymphadenitis are caused by M. avium isolates belonging to the Mav-B sequevar (11). The isolate we describe here must be added to a long list of organisms similar to M. avium that have been identified as causes of lymphadenitis in children (1, 6, 8-10, 12, 15, 19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of MAC lymphadenitis are caused by M. avium isolates belonging to the Mav-B sequevar (11). The isolate we describe here must be added to a long list of organisms similar to M. avium that have been identified as causes of lymphadenitis in children (1, 6, 8-10, 12, 15, 19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…In AIDS patients, MAC is the most common nontuberculous mycobacteria causing disease, especially in developed countries, and usually produces disseminated infections (8,16). However, MAC also causes infection in immunocompetent individuals with underlying pulmonary disease and in children with lymphadenitis or cystic fibrosis (10,14,16).…”
mentioning
confidence: 99%
“…Numbers next to sequevar names represent the total number of subject isolates (case or control) that belonged to this sequevar group. (3,19), is better able to invade and replicate inside macrophages than M. intracellulare (14), and has been associated with more invasive forms of MAC disease (3,10,21,27). Our data differ from the findings of a recent study by Han et al, who found that M. avium (identified by 16S rRNA sequencing) isolated from clinical specimens was actually less likely to be associated with pulmonary disease than was M. intracellulare (9).…”
mentioning
confidence: 99%